2013
DOI: 10.1111/jnc.12617
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid biosynthesis from glutamate and glutamine is specifically induced in neuronal cells under hypoxia

Abstract: Hypoxia is involved in many neuronal and non-neuronal diseases, and defining the mechanisms for tissue adaptation to hypoxia is critical for the understanding and treatment of these diseases. One mechanism for tissue adaptation to hypoxia is increased glutamine and/or glutamate (Gln/Glu) utilization. To address this mechanism, we determined total Gln/Glu incorporation into lipids and fatty acids in both primary neurons and a neuronal cell line under normoxic and hypoxic conditions and compared this to non-neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 82 publications
4
37
0
Order By: Relevance
“…The hypoxic treatment was as described earlier (Brose et al, 2014). Briefly, the cells were preconditioned by replacing the growth medium with serum-free minimum essential media (MEM) and incubating in 19% O 2 (Normoxia) or 1% O 2 (Hypoxia) in 5% CO 2 at 37°C using nitrogen gas to purge the oxygen.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The hypoxic treatment was as described earlier (Brose et al, 2014). Briefly, the cells were preconditioned by replacing the growth medium with serum-free minimum essential media (MEM) and incubating in 19% O 2 (Normoxia) or 1% O 2 (Hypoxia) in 5% CO 2 at 37°C using nitrogen gas to purge the oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have discovered a previously unknown and neuron-specific mechanism for utilizing anaerobic metabolism during hypoxia. We have found that hypoxic-stressed neurons have a unique response of dramatically increased fatty acid (FA) synthesis from glutamine and glutamate (Gln/Glu) (Brose et al, 2014). However, the biochemical significance of this pathway in neuronal adaptation to hypoxia is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glu has been described as a more "preferred" substrate for fatty acid synthesis than Gln. [56][57][58][59][60] In a pilot study by H. Baran et al, [61 an increase in KYNA level had a direct correlation with the severity of hypoxia. KYNA levels in tissues increased by 44% after 5min of asphyxia and 302% after 20min of asphyxia (the critical time limit of survival).…”
Section: Rgn and Hypoxiamentioning
confidence: 99%